2004
DOI: 10.1128/jb.186.24.8433-8442.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Locus Necessary for Rhamnose Uptake and Catabolism in Rhizobium leguminosarum bv. trifolii

Abstract: Rhizobium leguminosarum bv. trifolii mutants unable to catabolize the methyl-pentose rhamnose are unable to compete effectively for nodule occupancy. In this work we show that the locus responsible for the transport and catabolism of rhamnose spans 10,959 bp. Mutations in this region were generated by transposon mutagenesis, and representative mutants were characterized. The locus contains genes coding for an ABC-type transporter, a putative dehydrogenase, a probable isomerase, and a sugar kinase necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 61 publications
6
73
0
Order By: Relevance
“…(Table 3). Similar results were reported by Acosta and Martinez [27] and Richardson et al [28]. In these reports, Rhizobium strains were isolated from nodules of legumes growing in pesticide contaminated soils.…”
Section: Selection and Identification Of Bacterial And Fungal Strainssupporting
confidence: 88%
“…(Table 3). Similar results were reported by Acosta and Martinez [27] and Richardson et al [28]. In these reports, Rhizobium strains were isolated from nodules of legumes growing in pesticide contaminated soils.…”
Section: Selection and Identification Of Bacterial And Fungal Strainssupporting
confidence: 88%
“…The bacterial strains and plasmids used and generated in this work are listed in Table 1. S. meliloti strains were routinely grown at 30 uC on complex LuriaBertani (LB) medium or defined Vincent's minimal medium (VMM), as previously described (Sambrook et al, 1989;Vincent, 1970;Richardson et al, 2004). Carbon sources used in defined media were filter-sterilized and used at a final concentration of (Mulligan & Long, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Overnight cultures at mid-exponential phase were then subcultured into fresh medium of the same type, and grown to OD 600~0 .3, before being assayed as described by Miller (1972). Richardson et al (2004), with the following modifications. Cells were grown in defined media containing the appropriate carbon source(s), washed twice, and then resuspended in defined media with the original carbon source(s) (omitting arabinose or glucose as necessary) to OD 600 0.1-0.3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that the Rlt nodule strains belonging to defined genetic groups and varying in the plasmid profile differ also in metabolic capabilities and symbiotic effectiveness with clover [95]. It was also demonstrated that Rlt mutants in plasmid-located rhamnose utilization genes were significantly impaired in nodulation competitiveness [96,97]. The rhamnose catabolic genes were inducible by clover root extracts, suggesting their important role for early stages of the interaction of Rlt with the host plant.…”
Section: Rhizobial Plasmids Structure Gene Content and Impact On Bacmentioning
confidence: 99%